Environmental drivers of litter- and soil-dwelling springtail communities across European forests, assessed by morphotaxonomy and soil DNA metabarcoding - Ivano Brunner; Beat Frey; Maria J.I. Briones; Jérome Cortet; Xavier Domene; Juliane Filser; Aline Frossard; Davey L. Jones; Paul Henning Krogh; Juha Mikola; Olaf Schmidt; José Paulo Sousa; et al. (Applied Soil Ecology, 2026)

Polyethylene transformation by a psychrotolerant Rhodococcus strain assessed by transcriptomics and 13C-isotope tracing - Anja Werz; Ivano Brunner; Weihong Qi; Matthias Saurer; Marco M. Lehmann; Jan Kühnel; Beat Stierli; Beat Frey (Journal of Hazardous Materials, 2026)

Seasonality of microbial functional potentials and community diversity in high-Arctic tundra soils - Aline Frossard; Ekaterina Pushkareva; Vivien Hotter; Pascal A. Niklaus; Bjorn Tytgat; David Velazquez; Madgalene Adamczyk; Beat Stierli; Antonio Quesada; Mette M. Svenning; Ulf Karsten; Elie Verleyen; et al. (Soil Biology and Biochemistry, 2026)

Earthworm and enchytraeid indicator taxa of different land-use types identified using soil DNA metabarcoding - Jessica Cuartero; Maria J.I. Briones; Basil M. Rast; Beat Stierli; Claudia Maurer-Troxler; Anna-Sofia Hug; Franco Widmer; Jiří Schlaghamerský; Beat Frey (Applied Soil Ecology, 2025)

Metatranscriptomic responses of High-Arctic tundra soil microbiomes to carbon input - Gilda Varliero; Aline Frossard; Weihong Qi; Beat Stierli; Beat Frey (Soil Biology and Biochemistry, 2024)

Microbial dynamics in soils of the Damma glacier forefield show succession in the functional genetic potential - Maomao Feng; Gilda Varliero; Weihong Qi; Beat Stierli; Arwyn Edwards; Serina Robinson; Marcel G. A. van der Heijden; Beat Frey (Environmental Microbiology, 2023)
Glacier retreat is a visible consequence of climate change worldwide. Although taxonomic change of the soil microbiomes in glacier forefields have been widely documented, how microbial genetic potential changes along succession is little known. Here, we used shotgun metagenomics to analyse whether the soil microbial genetic potential differed between four stages of soil development (SSD) sampled along three transects in the Damma glacier forefield (Switzerland). The SSDs were characterized by an increasing vegetation cover, from barren soil, to biological soil crust, to sparsely vegetated soil and finally to vegetated soil. Results suggested that SSD significantly influenced microbial genetic potential, with the lowest functional diversity surprisingly occurring in the vegetated soils. Overall, carbohydrate metabolism and secondary metabolite biosynthesis genes overrepresented in vegetated soils, which could be partly attributed to plant–soil feedbacks. For C degradation, glycoside hydrolase genes enriched in vegetated soils, while auxiliary activity and carbohydrate esterases genes overrepresented in barren soils, suggested high labile C degradation potential in vegetated, and high recalcitrant C degradation potential in barren soils. For N‐cycling, organic N degradation and synthesis genes dominated along succession, and gene families involved in nitrification were overrepresented in barren soils. Our study provides new insights into how the microbial genetic potential changes during soil formation along the Damma glacier forefield.

A decade of irrigation transforms the soil microbiome of a semi‐arid pine forest - Martin Hartmann; Ivano Brunner; Frank Hagedorn; Richard D. Bardgett; Beat Stierli; Claude Herzog; Xiamei Chen; Andreas Zingg; Elisabeth Graf‐Pannatier; Andreas Rigling; Beat Frey (Molecular Ecology, 2017)
The impact of climate change on the soil microbiome potentially alters the biogeochemical cycle of terrestrial ecosystems. In semi‐arid environments, water availability is a major constraint on biogeochemical cycles due to the combination of high summer temperatures and low rainfall. Here, we explored how 10 years of irrigation of a water‐limited pine forest in the central European Alps altered the soil microbiome and associated ecosystem functioning. A decade of irrigation stimulated tree growth, resulting in higher crown cover, larger yearly increments of tree biomass, increased litter fall and greater root biomass. Greater amounts of plant‐derived inputs associated with increased primary production in the irrigated forest stands stimulated soil microbial activity coupled with pronounced shifts in the microbiome from largely oligotrophic to more copiotrophic lifestyles. Microbial groups benefitting from increased resource availabilities (litter, rhizodeposits) thrived under irrigation, leading to enhanced soil organic matter mineralization and carbon respired from irrigated soils. This unique long‐term study provides new insights into the impact of precipitation changes on the soil microbiome and associated ecosystem functioning in a water‐limited pine forest ecosystem and improves our understanding of the persistency of long‐term soil carbon stocks in a changing climate.

High spatial resolution measurements in lake sediments with PVC based liquid membrane ion‐selective electrodes - Beat Müller; Kerst Buis; Ruth Stierli; Bernhard Wehrli (Limnology and Oceanography, 1998)
Ion‐selective liquid membrane electrodes for Ca 2+ , CO 3 2− , NH 4 + , NO 3 − , NO 2 − , and pH have been miniaturized and their characteristics evaluated in view of their application in sediment pore water of lakes. PVC membranes were prepared in polyethylene pipette tips with an end diameter of 0.6 mm. This is a simple method to produce inexpensive disposable ion‐selective electrodes for various applications. Detection limits were 1 µM for Ca 2+ , CO 3 2− , NH 4 + , and NO 3 − , and 10 µM for NO 2 − . The pH sensor was linear in the pH range of 4–11. Selectivities for Ca 2+ , CO 3 2− and pH are high enough for the application in seawater. The sensors for NH 4 + , NO 3 − , and NO 2 − in their low concentration range experience interferences from K + , SO 4 2+ , and HCO 3 − , respectively, in lake pore water. Reproducibility in pure solutions is between 20.2 and 20.6 mV, The applicability of the miniaturized sensors are demonstrated in measurements of concentration gradients across the sediment‐water interface in sediment cores of several lakes.